INTELLIGENT TRAFFIC OPTIMIZATION SYSTEM USING ANFIS, GENETIC ALGORITHMS, AND DEEP REINFORCEMENT LEARNING: A SYSTEMATIC LITERATURE REVIEW - Jacob Dodo, Enoch Jacob DODO; Onwodi, Gregory2,; Okure Obot,; Isaac, Samson, (FUDMA JOURNAL OF SCIENCES, 2025)
This systematic literature review examines the state of intelligent traffic optimization systems integrating Adaptive Neuro-Fuzzy Inference Systems (ANFIS), Genetic Algorithms (GA), and Deep Reinforcement Learning (DRL). Spanning the period 2012–2025, the review synthesizes methodologies, applications, performance metrics, and emerging trends. The convergence of these computational intelligence techniques offers promising pathways for addressing urban mobility challenges by optimizing traffic flow, reducing congestion, and enhancing safety. Key findings reveal that hybrid frameworks significantly outperform single-method models, achieving up to 65% efficiency gains. The study concludes with future research directions emphasizing scalability, real-world deployment, and sustainability integration.
Keywords: ANFIS, Genetic Algorithm, Deep Reinforcement Learning, Traffic Optimization, Urban Mobility